Comparative Analysis of Capillary vs Venous Blood for Serologic Detection of SARS-CoV-2 Antibodies by RPOC Lateral Flow Tests - Morshed, Muhammad (Open Forum Infect Dis, 2021)
A comparison of rapid point-of-care serology tests using finger prick and venous blood was done on 278 participants. In a laboratory setting, immunoglobulin G (IgG) sensitivity neared 100%; however, IgG sensitivity dramatically dropped (82%) in field testing. Possible factors include finger prick volume variability, hemolysis, cassette readability, and operator training.